Kenan Görgün and the Turkish Legacy of a Belgian Writer ClujShorts International Film Festival - RĂCHIȚEANU, Simina (Studia Universitatis Babeș-Bolyai Dramatica, 2015)
The search of one’s personal identity, a classic theme approached by literature and arts, is continuously given new shapes and nuances as the perks of global capitalism allow individuals to have access to a variety of experiences all across the world. Travelling from one country to another, getting in touch with several (sometimes opposite) cultures has become quite common and it leads to more and more people gaining new perspectives. But, at the same time, transnational migration is a phenomenon which dissipates the borders of national and cultural norms, since so many people claim to belong to more than one society. Thus, at a constant speed, new issues need to be (re)discussed, issues of significant importance for artists, critics and scholars altogether.